Terminologi Semantik Al-Quran Terhadap Kata-kata Kunci: Studi Pada Kata al-Khusyu' - Muhammad Zikri; Nurhikma Nurhikma (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
The uniqueness of Islam lies in the fact that Islam itself is a religion that is based on a classical text, namely the Koran. The role of Muslim leaders is very important, and they make themselves reformers in understanding the text of the Koran, both by interpreting the Koran as a whole, thematically and so on. To understand the message of a Qur'anic text, a special formulation is needed to achieve a perfect understanding. One of them is the semantics of the Qur'an. This research is a literature review (library research) which is included in the category of historical textual research on manuscripts, the material object of this research is the Koran related to the terminology of the key word: al-khusyu'. In this study, descriptive and analysis-synthesis methods were used. Descriptive methods were mainly used to collect data and carry out an inventory of the word al-khusyu' in the Qur'an. While the analysis-synthesis in question is researching and reading in depth so as to get maximum results. The word al-khusyu' in the Qur'an has many meanings, including: submission to the teachings of the Prophet Muhammad, submission to Allah, submission of the soul, voice, sight, obedience to the commands of Allah, humility to Allah, solemn in reaching Allah swt, turning his eyes towards the lower.